2012
DOI: 10.1111/j.1525-1446.2011.01003.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurse Home Visitors' Perspectives of Mandatory Reporting of Children's Exposure to Intimate Partner Violence to Child Protection Agencies

Abstract: Training about maltreatment reporting procedures in home visitation programs should focus on the interpretation of child maltreatment laws as well as collaborations with local child protection service agencies to determine if children's exposure to IPV is reportable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 38 publications
1
11
0
5
Order By: Relevance
“…They discussed both everyday issues and problems related to child development with the parents at a child health center, but they failed to discuss relationship issues sufficiently. These results also agree with earlier results [ 9 , 25 27 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…They discussed both everyday issues and problems related to child development with the parents at a child health center, but they failed to discuss relationship issues sufficiently. These results also agree with earlier results [ 9 , 25 27 ].…”
Section: Discussionsupporting
confidence: 94%
“…However, at the identifying and intervening levels, they were not able to apply their willingness in real situations. According to earlier studies [ 9 , 25 , 27 ], PHNs feel that they are in a good position to take the actions needed but they need more training on applying their knowledge in real situations when working with children and families.…”
Section: Discussionmentioning
confidence: 99%
“…These findings complement previous research that has examined nurse home visitors' attitudes and intended reporting behaviours for both IPV and children's exposure to IPV (Davidov et al . ,c). In those studies, home visitors indicated that they were more likely to consider children's exposure to IPV to be indicative of child maltreatment vs. IPV perpetrated against a woman who was pregnant and were more likely to report the former scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed information about the methodology and design for the current study can be found elsewhere (Davidov et al . ,c). Data were collected in April/May 2010.…”
Section: The Studymentioning
confidence: 99%
See 1 more Smart Citation